Retrospective study of intravascular large B-cell lymphoma cases diagnosed in Quebec: A retrospective study of 29 case reports. Issue 5 (February 2017) - Brunet, Vanessa; Marouan, Sofia; Routy, Jean-Pierre; Hashem, Mohamed Amin; Bernier, Vincent; Simard, Raynald; Petrella, Tony; Lamarre, Louis; Théorêt, Gilles; Carrier, Christian; Knecht, Hans; Fleury, Isabelle; et al.
Abstract: Introduction: Intravascular large B-cell lymphoma (IVL) is an extremely rare malignancy, mainly studied through European and Asian series. Due to the low incidence of this condition, our understanding of the clinical presentation as well as the management of IVL relies on a limited number of patients. We report the largest North American study to date on IVL with 29 cases from Quebec hospital diagnosed between 1990 and 2016. The aim of our study is to describe the clinical presentations, diagnostic and staging procedures, therapeutic management and clinical outcomes of IVL patients in our population and compare the disease phenotype to European and Asian series reported. In our cohort, all patients had stage IV IVL at diagnosis, with a median age of 66.7 years (range 47.2–90.8). Clinical presentation was characterized by constitutional symptoms (100%), poor ECOG-PS (100% ≥ 2), cytopenias (93% anemia), and elevated lactate dehydrogenase (97%) and C-reactive protein (96%). Our cohort presented with mainly cutaneous and neurological symptoms. However, neurological involvement (75.9%) was predominant and no "cutaneous variant" was observed; this differs from European literature, where "classical" IVL is reported with mainly cutaneous involvement. Two of our Caucasian patients presented "Asian variant" IVL; this observation is not unusual, as cases of "classical" IVL have been reported in Asians and "Asian variant" IVL has been reported in Europeans. All patients were classified according to their immunophenotypic features in 3 different subgroups (CD5 + or CD5 − CD10 +, CD5 − CD10 −, CD5 + CD10 − ) with no difference in outcome. Finally, 62% of our cohort received anthracycline-based chemotherapy and 53% of them achieved a complete response. After a median follow-up of 328 days, OS at 3 years was 42.7% for the entire cohort and 47.4% for the cases with in vivo diagnosis. Conclusion: Unlike European studies on "classical" IVL, our study showed that the French Canadian presentation of this subtype of IVL is more frequently observed with neurological rather than cutaneous involvement. Finally, an early diagnosis is of primary importance since almost a quarter of patients receive a post-mortem diagnosis. A prompt diagnosis allows the introduction of an early treatment, associated with a CR in 53% of patients.